Perilaku Ikhlas Alumni Santri Siap Guna Daarut Tauhiid: Fenomenologi - Lara Ekamia, Gusti; yusuf L.N, syamsu; Budiman, Nandang (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2023)
Sincere behavior is an attitude that is highly recommended in Islam, because a sincere attitude is worth worshipping, and sincere people will be loved by Allah Subhanahu Wa Ta'ala. In addition, sincere behavior can be a solution to moral problems in Indonesia. This article aims to find out the form of sincere behavior of the alumni of Santri Siap Guna Daarut Tauhiid (SSG-DT) after attending the Education and Training of Santri Siap Guna Daarut Tauhiid (SSG-DT). This study uses a qualitative approach to phenomenology. Data analysis used thematic analysis. Data was collected through in-depth interviews. Participants in this study amounted to one person, namely a woman aged twenty-five years old who is an alumni of Santri Siap Guna Daarut Tauhiid (SSG-DT) batch 38. The name of the participant in this study is written as Teh K to protect the participant's personal identity. The results of this study showed that the sincere behavior of the alumni of Santri Siap Guna Daarut Tauhiid (SSG-DT) was a form of behavior. Sincere in the family, peers, and society. One example of sincere behavior towards mothers is that every time they receive a monthly salary from a teaching place, namely Madrasah Ibtidaiyah (MI), they buy their mother's favorite shoes. Teh K always gives half the salary she gets from teaching at Madrasah Ibtidaiyah to her mother. Teh K also often helps his mother sell in the shop or offers his mother's merchandise via Whatsapp. Sometimes Teh K deliberately invites her mother to shop at a mini market near her house to buy necessities such as toothpaste, laundry soap, white bread, milk, etc. The implications of sincere behavior for the alumni of Santri Siap Guna Daarut Tauhiid (SSG-DT) are so that students can get closer to Allah and make Allah the only giver of rewards, hope only in Allah, help without expecting anything in return, and behave as a student in general.